2010
DOI: 10.1016/j.vaccine.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

B cell responses to H5 influenza HA in human subjects vaccinated with a drifted variant

Abstract: B cell responses after immunization with a drifted H5 influenza/A/Vietnam/1203/04 vaccine were characterized in the peripheral blood of human subjects primed with experimental recombinant H5 influenza A/Hong Kong/156/97 vaccine. Antibody secreting cells were assayed by ELISPOT against a panel of recombinant hemagglutinin and control proteins. Increased frequencies of H5 HA specific antibody secreting and memory B cells could be observed within 7 days of re-vaccination. Furthermore, these responses were cross-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…We selected an elderly population and specifically focused on influenza A/H1N1-specific memory B cells. Our data support the conclusion that the B cell ELISPOT assay is a highly effective method to detect influenza A/H1N1-specific B cells after vaccination (1,12,23). Several strains of the influenza virus exist due to the known variances in the HA and NA surface antigens.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We selected an elderly population and specifically focused on influenza A/H1N1-specific memory B cells. Our data support the conclusion that the B cell ELISPOT assay is a highly effective method to detect influenza A/H1N1-specific B cells after vaccination (1,12,23). Several strains of the influenza virus exist due to the known variances in the HA and NA surface antigens.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, coating the plates with recombinant H1 viral glycoprotein instead of whole influenza virus would exclusively detect H1-specific B cells, thus measuring the B cell response against the major viral surface protective antigenthe hemagglutinin. This type of assay is observed in the work of Baer et al, who optimized a B cell ELISPOT detection of influenza-specific H5-specific B cells (1). However, the H1 protein is the primary surface antigen known for initial cellular interaction, and neuraminidase (N1) is responsible for the hydrolysis of the sialic acid-H1 complex for viral release.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports from human studies have shown that prior immunization with an rH5 HA (A/Hong Kong/156/97) vaccine results in a “boosted” response to the drift variant VN04 upon re-vaccination with a single dose of A/VN/1203/04 split vaccine [20, 21]. To study how prior immunity to H5 HA can influence the antibody response elicited upon vaccination with rHA derived from a different H5 virus clade, an immunization schedule that included a drifted variant of rH5 HA was developed (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence supporting the idea of pre-vaccination is limited, but studies in humans suggest that immunization with baculovirus-expressed recombinant hemagglutinin (rHA) H5N1 vaccine (clade 0) primes the immune system, resulting in clinically significant serological responses following a single dose of a inactivated H5N1 vaccine containing a drifted (clade 1) virus [20]. Further studies, using the same cohort of subjects, have revealed that there is a population of memory B cells that are specific and cross-reactive to both H5 HA antigens and respond rapidly to vaccination with the drifted variant [21]. These studies show that pre-vaccination does not preclude the ability to generate new and/or cross-reactive cellular and antibody responses to the new drifted H5.…”
Section: Introductionmentioning
confidence: 99%
“…Both animal models and human studies which make use of peripheral blood mononuclear cell (PBMC) sampling have long been used to study the immune response to influenza infection (Baer et al, 2010; Falsey et al, 2009; Halliley et al, 2010). Animal models have some advantages over human studies, including high frequency sampling of multiple tissues (Miao et al, 2010) and the ability to block or deplete individual immune response elements such as the CD8 effector and B cell mediated antibody responses (Teijaro et al, 2010; Zeng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%